PENGARUH LATIHAN UPHILL TERHADAP HASIL AKSELERASI 30 METER CLUB ATLETIK GELAGAH WANGI DEMAK - Kardiyono Kardiyono; Budi Darsono (LP2M, 2017)
This study aimed to find out is there any influence of doing uphill acceleration run with aslope angle of 10 degrees to acceleration results ran 30 meters at the athletics club GelagahWangi Demak. The method used was experimental. The population in this study were allsprint athletes at the athletics club Gelagah Wangi Demak. In order to achieve the objectivesof this study, the researcher used matchet subject design and the research instruments includean exercise program of uphill acceleration run with a slope angle of 10 degree, a trainingprogram of uphill acceleration run with a slope angle of 30 degree and the ability test to run30-meter acceleration. The Data were analyzed using T test. The results of the study show thatthe acceleration uphill training run with a slope of 10 degrees and 30 degrees can increasethe acceleration of sprint athletes at the athletics club Gelagah Wangi Demak. The resultsalso show that there are some differences in the increase of two groups, group I and group II.It can be concluded that a training program of uphill acceleration run with a slope angle of30 degree gives greater increase than the 10 degrees in the 30-meter acceleration. Based onthe result of this research, the writer expected to provide a solution for trainers in order toincrease the running speed in sprinting.Key Words: uphill , acceleration run, athletics